2011
DOI: 10.1080/02673037.2011.559750
|View full text |Cite
|
Sign up to set email alerts
|

‘Reaching the Parts Other Grants Don't Go?’ Supporting Self-provided Housing in Rural Scotland

Abstract: Ensuring that rural areas of the UK have sufficient affordable houses in reasonable condition has long challenged policy makers. Previous research shows that rural housing has demand characteristics and faces supply constraints that have proven difficult to balance. The paper reports on the reasons why an innovative subsidy has achieved some success in overcoming barriers to provision in rural Scotland. It is argued that the subsidy has boosted effective demand and tackled a major supply constraint, namely lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
(29 reference statements)
0
4
0
1
Order By: Relevance
“…Another recent trend in the literature has been to look at the issue of housing and transport disadvantage outside the major or capital cities. While Airola and Parker (1982) and Blunden et al (1998) have shown how the 'rural suburb' has grown and attracted in-migration in the US and Europe, Mikelbank (2004) and Morgan and Satsangi (2011) reveal how the current stock of housing in these areas cannot keep up with the population growth and has increased the level of housing disadvantage.…”
Section: Introductionmentioning
confidence: 99%
“…Another recent trend in the literature has been to look at the issue of housing and transport disadvantage outside the major or capital cities. While Airola and Parker (1982) and Blunden et al (1998) have shown how the 'rural suburb' has grown and attracted in-migration in the US and Europe, Mikelbank (2004) and Morgan and Satsangi (2011) reveal how the current stock of housing in these areas cannot keep up with the population growth and has increased the level of housing disadvantage.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst this article achieves our aim of refocusing attention on the importance of geography in discussions of 'Generation Rent', to fully unpack the nuanced experiences of young people would require a larger stratified sample drawing on participants from a wider range of rural contexts to consider socio-spatial variation. This is important given that rural areas contain housing options that are not as typically found in urban areas such as Community Land Trusts, crofting and self-build (Morgan & Satsangi, 2011;Moore, 2015). Furthermore, housing strongly overlaps with land ownership and this is salient within rural contexts as private land owners exert great influence over housing and community development (McKee, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Przedmiotem badania w kontekście mieszkalnictwa na obszarach wiejskich jest głównie sytuacja mieszkaniowa i jej przestrzenne zróżnicowanie (Ciura, 2010;Oleńczuk-Paszel, Sompolska-Rzechuła, 2017;Szymańska, Biegańska, 2011;Murawska, 2012;Gibas, Heffner, 2018;Bański, 2008b;Siedlecka, 2018), preferencje mieszkaniowe seniorów (Jancz, 2019), przemiany zachodzące w gminach wiejskich w wyniku procesów suburbanizacji (Musiał-Malago, 2016). Znacznie więcej uwagi poświęca się polityce mieszkaniowej prowadzonej na obszarach wiejskich w Ameryce Północnej, Australii oraz Europie Zachodniej w kontekście jej kształtowania z perspektywy zarówno zaspokajania potrzeb mieszkaniowych społeczności lokalnej, jak i strategii rozwojowych obszarów wiejskich (Clark, 2012;Scott, Murray, 2009;Gkartzios, Scott, 2009;Gkartzios, Scott, 2014;Strohm i in., 2016;Reeder i in., 1987;Satsangi, Dunmore, 2003;Morgan, Satsangi, 2011;Kordel, Neumann, 2023).…”
Section: Wprowadzenieunclassified